Intelligent metasurface sensors - Li, Lianlin; Zhao, Hanting; Cui, Tie Jun ca. 20./21. Jh (Elements of emerging theories and technologies in metamaterials, 2023)
Intelligent electromagnetic (EM) sensing is a powerful contactless examination tool in science, engineering and military, enabling us to 'see' and 'understand' visually invisible targets. Using intelligence, the sensor can organize by itself the task-oriented sensing pipeline (data acquisition plus processing) without human intervention. Intelligent metasurface sensors, synergizing ultrathin artificial materials (AMs) for flexible wave manipulation and artificial intelligences (AIs) for powerful data manipulation, emerge in response to the proper time and conditions, and have attracted growing interest over the past years. The authors expect that the results in this Element could be utilized to achieve the goal that conventional sensors cannot achieve, and that the developed strategies can be extended over the entire EM spectra and beyond, which will produce important impacts on the society of the robot-human alliance